Real Polynomial Maps and Singular Open Books at Infinity - Santos, Raimundo N. Araújo Dos; Chen, Ying; Tibăr, Mihai (MATHEMATICA SCANDINAVICA, 2016)
We provide significant conditions under which we prove the existence of stable open book structures at infinity, i.e. on spheres S^m-1_R of large enough radius R. We obtain new classes of real polynomial maps R^m → R^p which induce such structures.